The Effect of Using Design Thinking Concept in Improving the Inpatient Pharmaceutical Dispensing System to Increase Service Efficiency: a Study at Lampang Hospital - เหลืองจิรโณทัย, ปิยวรรณ (Journal of Health Science of Thailand, 2025)
The current inpatient dispensing system frequently necessitates an extended period of time to ensure that medications are delivered to patient wards, which results in delayed access to medicine. As a result, healthcare professionals are frequently compelled to work overtime, which has a significant impact on their personal lives and families. Design thinking was implemented as the framework for improving the system to confront these challenges. The objective of this cross-sectional study was to assess the influence of implementing design thinking into the inpatient pharmacy workflow. The initial phase of data collection, which covered from February to May 2022, involved the evaluation of staff requirements and the analysis of the system. This was conducted during official working hours. The second phase, which covered from June to September 2022, was dedicated to the implementation and testing of the redesigned system. The evaluation emphasized three critical components: the duration of medication delivery for continuous prescriptions, the safety of the system (as determined by dispensing errors), and the working hours of the staff. To evaluate performance during the two periods, descriptive statistics, t-tests, and numerous regression analyses were carried out. Period 1 and period 2 comprised 78 and 81 working days, respectively. The average number of prescriptions during working hours was 1,288.8±157.7, and the average number of orders made was 1,293.6±84.3 (p=0.809). There was an average of 468.9±35.2 and 512.8±47.8 orders for continuous prescriptions, which included oral medications prepared by a robotic dispensing system and injectable drugs prepared manually by staff (p<0.001). The time required to process continuous prescriptions decreased from 180.4±34.4 minutes in period 1 to 171.2±24.7 minutes in period 2, indicating a significant decrease of 19 minutes (adjusted p<0.001). Dispensing errors were comparable in number (53 vs. 55). Nevertheless, the total working time from the receipt of prescriptions to the delivery of medication to the wards experienced a significant decrease, from 503.1±21.5 minutes to 492.9±10.5 minutes (p<0.001). In summary, the inpatient dispensing system’s workflow efficiency was significantly improved, overtime labor was reduced, and service delivery was improved through the application of design thinking.